Loss of CD45RA and gain of CD45RO after in vitro activation of lymphocytes from HIV-infected patients. - Pinto, L (1991)
T-lymphocyte activation is accompanied by a loss of CD45RA determinant and gain of CD45RO marker. Previous work suggests that the CD45RO population could represent the T-cell memory pool since it contains most of the cells that can respond to recall soluble antigens. A selective loss of memory T cells was recently found in early stages of human immunodeficiency virus (HIV) infection, which could contribute to the qualitative defects observed in HIV-infected patients. In order to investigate whether HIV infection could induce an alteration in the process of differentiation from naive cells to cells with a memory phenotype, we studied the expression of CD45RA and CD45RO in CD4+ and CD8+ lymphocytes, by flow cytometric analysis, after mitogenic stimulation of mononuclear cells from patients with HIV infection. These preliminary results suggest that after in vitro activation the CD4+ and CD8+ populations from HIV-infected patients lose the CD45RA marker and concomitantly acquire the CD45RO determinant in the same way as shown for the healthy control population studied simultaneously. Thus, it appears that an alteration in the process of conversion of CD45RA into CD45RO does not contribute to the defects observed in the memory T-cell population in HIV infection.